PERENCANAAN PENGEMBANGAN PELABUHAN TANJUNG EMAS SEMARANG - Aditya Perwira Aji; Brahmandita Paramarta; Sutarto Edhisono; Dwi Kurniani (Jurnal Karya Teknik Sipil, 2013)
As one of the strategic port of Tanjung Emas Port in Semarang Indonesia can not be separated from a variety of problems. From the analysis, in 2012 the capacity of the Port of Tanjung gold almost exceeded the maximum limit. In the container dock and public piers ideal has exceeded its ideal capacity. Protection of the pier from the brunt of a wave also not enough. Wave height reaches 71 cm in the dock being critical limit allowed is 50 cm. Another issue that still has not been able to overcome the level of land subsidence in the port area is very rapid at 14, 63 cm / year, so many areas in  lower elevation of the sea level . Because of that, rob at high tide occurs in some port areas. To overcome these shortcomings and to develop. From the analysis planned, towards the development of the Port of Tanjung Emas include lengthening container dock along 300 mx 25 m, the expansion of container yard area of 15 hectares, the elongation of breakwater along 150 m and the polder planning system as a protection against tidal.